Petrogenesis of basalts for Sangxiu Formation in the central segment from Tethyan Himalayas: Plume-lithosphere interaction - Dicheng, Zhu; Guitang, Pan; Xuanxue, Mo; Zhongli, Liao; Liquan, Wang; Xinsheng, Jiang; Zhidan, Zhao (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 125-7